Minnesota's Geology - Ojakangas, Richard W. (Book collections on Project MUSE., 1982)
Minnesota's Geology provides a history of the past 3.5 billion years in the area's development. In accessible language, Minnesota-based geologists Richard W. Ojakangas and Charles L. Matsch tell the story of the state's past and offer a guide for those who want to read geological history firsthand from the rocks and landscapes of today. "Minnesota's Geology sets a standard of excellence for books about the geology of a region. . . an unusually well-written and well-balanced book." Science Books and Films.